CHARACTERS OF MINANGKABAU PEOPLE THROUGH EXPRESSION AS SEEN ON POLITICAL ASPECTS: KARAKTER ORANG MINANGKABAU MELALUI UNGKAPAN DITINJAU DARI ASPEK POLITIK - M Sayuti; Ali Mardius; Efrianto Efrianto (Jurnal Kata, 2022)
This study aims to describe the character of the Minangkabau community through their expressions reviewed from the political aspect. This is a descriptive qualitative research, sample of 60 people are randomly assigned to represent traditional stakeholders. The research instrument is a questionnaire. The informen came from the core area of Minangkabau. It was found that the character of the Minangkabau people was based on two systems; the Koto Piliang harmony system pioneered by Datuk Ketumanggungan and the Bodi Caniago harmony system was pioneered by Datuk Perpatih Nan Sabatang political system emanates from the earth. These opposing systems produce two systems based on: democracy, egalitarianism, and social justice aspects. In political democracy, Minangkabau people making decisions through deliberation to reach consensus, which is expressed by "bulat air ke pembuluh, bulat kata ke mufakat". Politically egalitarian they put themselves wherever they are which is expressed by "di mana bumi dipijak di situ langit dijunjung". In terms of socio-political justice, through the spirit of trading habit, they help each other by sharing their feelings and concerns, which are expressed as "berat sama dipikul ringan sama dijinjing."